The Effect of Internal Factors and Exchange Rate on Sharia Banking Liquidity in Indonesia - Muh. Syahru Ramadhan; Rizkiana Iskandar; Yeye Suhaety; Nurul Hayat (Journal of Business and Management Review, 2022)
Islamic banking is quite unique because it prioritizes its operational activities on financing distribution, this raises a phenomenon related to liquidity problems. This study aims to examine the influence of internal factors, namely capital, credit risk level, third party funds, and external factors, namely the excange rate on the liquidity level of Islamic banks in Indonesia. This study uses a quantitative approach using purposive sampling method in sampling. The test was carried out with multiple linear regression. The results showed that capital and credit risk level can affect liquidity. Meanwhile, third party funds and exchange rates are not proven in determining the level of liquidity of Islamic banks in Indonesia.